Ontogenetic shift in dietary preference and low dietary overlap in rohu (Labeo rohita) and common carp (Cyprinus carpio)in semi-intensive polyculture ponds - Rahman, Mohammad Mustafizur; Hossain, Md Yeamin; Jo, Qtae; Kim , Su-Kyoung; Ohtomi, Jun; Meyer, Carl G (Springer Japan, 2009)
In order to investigate ontogenetic changes in diet and diet overlap between rohu (Labeo rohita) and common carp (Cyprinus carpio) in polyculture ponds, food preferences of different size classes of these fishes were quantified. Rohu diet consisted of both phytoplankton and zooplankton, and there was a distinct ontogenetic shift in the relative importance of these food items. Zooplankton was the dominant food for rohu up to 20.6 cm total length (TL) and then gradually decreased in importance as fish grew. Phytoplankton was initially a minor component of rohu diet but gradually increased in importance and became the dominant food for rohu at 24.2 cm TL. Phytoplankton biovolume in rohu guts was positively correlated with fish size (TL). Chesson’s a indicated that rohu of all sizes preferentially selected Cladocera and avoided Cyanophyceae and Euglenophyceae. Young rohu initially preferred Rotifera and Copepoda but gradually switched to Bacillariophyceae and Chlorophyceae. Common carp diet consisted of phytoplankton, zooplankton,and benthic macroinvertebrates, but was dominated by benthic macroinvertebrates (63–92% of total diet). As common carp grew, the proportion of zooplankton ingested decreased and the proportion of benthic macroinvertebrates increased. Benthic macroinvertebrate biovolume in common carp guts was positively correlated with fish size. Common carp of up to 15.4 cm TL preferentially selected zooplankton, but common carp larger than 18.9 cm TL avoided this food item. Common carp of all sizes avoided phytoplankton. A low dietary overlap was found between rohu and common carp (Schoener overlap index: 0.08–0.35), probably due to ingestion of smaller quantities of zooplankton by the latter. Dietary overlap also decreased with increasing rohu and common carp size because of divergent ontogenetic shifts in dietary preferences of the two species.